Seminal vesicle status and its association with semen parameters in congenital bilateral absence of the vas deferens (CBAVD) - Iman Shamohammadi; Abdolreza Haghpanah; Ali Eslahi; Mohammad Ali Sadighi Gilani; Ali Adib; Seyyed Sadra Kashfi (Basic and Clinical Andrology)
Abstract Background Congenital bilateral absence of the vas deferens (CBAVD) is a rare condition associated with male infertility. CBAVD is often accompanied by other genitourinary anomalies, including abnormalities or agenesis of the seminal vesicles and kidneys. While it is expected that CBAVD always coexists with seminal vesicle agenesis due to a shared embryologic origin, some studies report the presence of seminal vesicles in certain CBAVD patients. This study aims to assess the status of seminal vesicles in CBAVD patients and explore the relationship between seminal vesicle presence and semen parameters. Methods In this multi-center, retrospective cross-sectional study, we reviewed data from 47 CBAVD patients diagnosed between 1994 and 2024. Data collected included demographic information (age, height, weight, BMI), physical examination findings (vas palpation), and imaging results (trans-rectal ultrasound for seminal vesicle status, abdominal and pelvic ultrasound for kidney status). Laboratory data included serum FSH, LH, and testosterone levels, as well as semen analysis results (pH, fructose, and volume). Patients were classified into three groups based on seminal vesicle status: bilateral agenesis, unilateral agenesis, and bilateral presence. Results Among the 47 CBAVD patients, 29 had bilateral agenesis of the seminal vesicles, 9 had unilateral agenesis, and 9 had bilateral presence. No significant differences were found between the groups regarding weight, height, BMI, or serum levels of LH, FSH, and testosterone. Additionally, semen analysis revealed that 89.4% of patients had abnormal pH, 93.6% had abnormal volume, and all patients had abnormal semen fructose. There were no significant differences between the groups in semen pH, fructose, or volume. Conclusion Our findings suggest that the presence or absence of seminal vesicles in CBAVD patients does not significantly affect semen parameters. This may be due to dysfunction of the seminal vesicles in those with a present organ.